An assessment of burden of hospital-acquired pneumonia among abdominal surgical patients in tertiary university hospital in Serbia: A matched nested case-control study - Taušan, Ðorde; Rančić, Nemanja; Kostić, Zoran; Ljubenović, Nenad; Rakonjac, Bojan; Šuljagić, Vesna (Frontiers in Medicine, 2022)
Background: In the population of abdominal surgical patients hospital-acquired pneumonia (HAP) significantly increases morbidity and mortality. Patients and methods: Through regular hospital surveillance of patients who received abdominal operations, we identified postoperative HAP from 2007 to 2015. In an initial nested case-control study, every surgical patient with HAP was compared with three control patients without HAP. Control patients were matched to the cases by age, the American Society of Anesthesiologists score, and type of surgical operation. Also, the patients with HAP, who died were compared with those who survived. Results: Multivariate logistic regression analysis revealed the length of hospital stay, stay in the intensive care unit, use of histamine-2-receptor antagonists (H2RA), use of proton-pump inhibitors (PPI), multiple transfusion and use of vancomycin were independently associated with the occurrence of HAP. Also, the use of mechanical ventilation and use of PPI were associated independently with the poor outcome of HAP. All Acinetobacter baumannii isolates were resistant to aminoglycoside antimicrobial agents and showed carbapenem resistance. The most frequently used antibiotics in patients with HAP and without HAP were vancomycin and metronidazole, respectively. Conclusion: Our study provided an insight into the burden of HAP in abdominal surgical patients, and highlighted several priority areas and targets for quality improvement.